Diagnostic accuracy of technetium-99m-octreotide in imaging neuroendocrine tumors, Oman hospital experience with literature review - Naima Al Bulushi (World Journal of Nuclear Medicine, 2019)
The aim of this observational cross-sectional study with retrospective review of the data is to evaluate the efficacy of using technetium-99m-octreotide (Tc-99m-OCT) in imaging neuroendocrine tumors (NETs) in our tertiary care hospital. A total of 58 patients had Tc-99m-OCT were identified in our database, from January 2013 to December 2016. Forty-one patients (age range of 15–75 years) meet our inclusion criteria, namely histopathology proven NETs, Tc-99m-OCT scan, computed tomography (CT), or magnetic resonance imaging (MRI) done in our institute for correlation. Twenty-three patients had true positive Tc-99m-OCT scan. In addition to the primary tumors, the octreotide scan revealed metastasis in the lung, liver, and retroperitoneal lymph nodes. The smallest lesion detected on octreotide scan was a 4-mm pulmonary nodule that was missed on lung window CT scan. The Tc-99m-OCT had 17 true negative, one false negative, and no false positive. The CT and MRI scans had 18 true positive, 17 true negative, 5 false negative, and one false positive. The overall sensitivity, specificity, accuracy, positive, and negative predictive values of Tc-99m-OCT scan were 96%, 100%, 97%, 100%, and 94%, respectively. Whereas those of CT and MRI were 78%, 94%, 85%, 94%, and 77%, respectively. Our diagnostic accuracy of Tc-99m-OCT is high. We recommend that, in addition to the conventional radiological investigations, Tc-99m-OCT scan, or other somatostatin receptor imaging (SSR) is a mandate for better and accurate staging of patients with NETs.